P2P lending in China: Role and prospects for the future. (21st June 2020) - Hsu, Sara; Li, Jianjun; Bao, Hong
Abstract: In the early days of development, the Chinese P2P lending industry grew rapidly due to financial constraints faced by small businesses and consumers and expanded under a lax regulatory environment. The industry filled a gap in demand for finance but was accompanied by increasing risks and poor business models. Regulation was put into place piecemeal, but large regulatory action was taken in 2018 to register P2P businesses and then, in 2019 to wind down the industry. The experience of China's P2P lending industry underscores the importance of assessing credit risk reducing operational risk under experienced financial management. Although China's P2P industry is dying away, lessons from the industry have helped to improve the structure of new fintech firms.